Applications of Carbon Dots in Optoelectronics - Evgeniia A. Stepanidenko; Elena V. Ushakova; Anatoly V. Fedorov; Andrey L. Rogach (Nanomaterials, 2021)
Carbon dots (CDs) are an attractive class of nanomaterials due to the ease of their synthesis, biocompatibility, and superior optical properties. The electronic structure of CDs and hence their optical transitions can be controlled and tuned over a wide spectral range via the choice of precursors, adjustment of the synthetic conditions, and post-synthetic treatment. We summarize recent progress in the synthesis of CDs emitting in different colors in terms of morphology and optical properties of the resulting nanoparticles, with a focus on the synthetic approaches allowing to shift their emission to longer wavelengths. We further consider formation of CD-based composite materials, and review approaches used to prevent aggregation and self-quenching of their emission. We then provide examples of applications of CDs in optoelectronic devices, such as solar cells and light-emitting diodes (LEDs) with a focus on white LEDs.